Biomass-derived carbon decorated by gold nanoparticles as efficient methanol electrochemical sensor. (1st August 2022) - Alsaiari, Mabkhoot; Ahmed, Jahir; Faisal, M.; Harraz, Farid A.
Abstract: Herein, we have demonstrated the successful combination of gold nanoparticles (AuNPs) and green carbon (GC) (biomass-derived) obtained from date seeds to detect methanol (MeOH) via a simple electrochemical approach. We have synthesized GC by pyrolysis method whereas AuNPs were deposited by the photochemical deposition technique. We have systematically characterized the Au@GC nanocomposite by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), FESEM, high-resolution transmission electron microscopy (HR-TEM), and Raman spectroscopy. In comparison to a bare glassy carbon electrode (GCE) or GC fabricated GCE, the newly-fabricated Au@GC nanocomposite modified GCE (Au@GC/GCE) has shown better performance in MeOH sensing. The proposed sensor exhibited excellent sensitivity (0.0143 μAmM −1 ), a lower detection limit (LOD = 0.39 mM at S/N = 3), and a wide linear dynamic range (LDR = 1–80 mM). This Au@GC/GCE sensor also showed good operational stability, reproducibility, and repeatability in MeOH detection. The research findings indicated the potential application of the Au@GC nanocomposite as an electroactive material for effective electrochemical sensing of environmental pollutants. Graphical abstract: Image 1 Highlights: Green carbon from date seeds via pyrolysis technique. Au-decorated green carbon nanocomposite via photo-deposition route. Au decorated green carbon nanocomposite as efficient methanol electrochemical sensor. Good sensitivity 0.0143 μAmM −1, low LOD 0.39 mM and wide range 1–80 mM. Excellent reproducibility, repeatability and stability of the modified electrode.